Schistosoma haematobium ova in human semen: a case report - Kazim R. Chohan, D.V.M, Ph.D; Crystal A. Kling, B.S; Timothy K. Byler, M.D (Elsevier, 2021)
Objective: To report a rare case of schistosomiasis observed during semen evaluation. Design: Case report. Setting: University hospital. Patient(s): A 30-year-old man referred for semen analysis. Interventions(s): None. Main Outcome Measures(s): Poor sperm motility and viability. Result(s): The patient produced 9.8 mL of brown colored semen with a bad odor. Total and progressive sperm motility were 9% and 2%, respectively. Sperm concentration was 112 million/mL. Microscopic semen evaluation showed slight sperm agglutination, a large number of Schistosoma haematobium ova, extensive debris, and a large numberot of amorphous cells. Approximately 20 million/mL of neutrophils were observed in the ejaculate. The sperm viability was extremely low (13%). Sperm morphology was 6% normal, and most abnormal sperm had coiled tails in addition to other abnormalities. Conclusion(s): A microscopic examination of semen from suspected Schistosoma haematobium-infected patients may not only help in confirming diagnosis but may also highlight the underlying infertility due to this infestation. Such cases are rarely observed in andrology laboratories; therefore, it is important to train all testing staff on rare semen samples.